Answer:
Note that the ratio 12 to 3 is said to be equivalent to the ratio 4 to 1, that is 12:3 = 4:1.
Answer:
1 1/4
1.25
Step-by-step explanation:
Answer:
(x - 6)(x + 3)
Step-by-step explanation:
Given
x² - 6x + 3x - 18 ( factor the first/second and third/fourth terms )
= x(x - 6) + 3(x - 6) ← factor out (x - 6) from each term
= (x - 6)(x + 3)
Answer:
opposite sides of a parallel are congruent.
Step-by-step explanation:
the symbol between AB and DC stands for "equal to", not parallel. boom roasted. (don't hate me if I'm wrong)
We have that
<span>tan(theta)sin(theta)+cos(theta)=sec(theta)
</span><span>[sin(theta)/cos(theta)] sin(theta)+cos(theta)=sec(theta)
</span>[sin²<span>(theta)/cos(theta)]+cos(theta)=sec(theta)
</span><span>the next step in this proof
is </span>write cos(theta)=cos²<span>(theta)/cos(theta) to find a common denominator
so
</span>[sin²(theta)/cos(theta)]+[cos²(theta)/cos(theta)]=sec(theta)<span>
</span>{[sin²(theta)+cos²(theta)]/cos(theta)}=sec(theta)<span>
remember that
</span>sin²(theta)+cos²(theta)=1
{[sin²(theta)+cos²(theta)]/cos(theta)}------------> 1/cos(theta)
and
1/cos(theta)=sec(theta)-------------> is ok
the answer is the option <span>B.)
He should write cos(theta)=cos^2(theta)/cos(theta) to find a common denominator.</span>